Awareness–Action Gap in Oral Health: The Relationship between Awareness and Caries Status, Periodontal Status, and Dental Visits among Prolanis Participants - Afina Hasnasari Heningtyas; Nadira Resya Nurhaliza; Rista Refdianti (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Oral health awareness is considered an important factor in maintaining oral health and encouraging the utilization of dental services. However, awareness does not always translate into actual health-seeking behavior, particularly among individuals with chronic diseases. This study aimed to analyze the relationships among oral health awareness, dental caries experience, periodontal status, and dental attendance among participants in the Chronic Disease Management Program (Prolanis). Materials and Methods: A cross-sectional study was conducted among 100 Prolanis participants. Oral health awareness was assessed using a structured questionnaire. Dental caries experience was measured using the Decayed, Missing, and Filled Teeth (DMF-T) index, while periodontal status was assessed using the Community Periodontal Index of Treatment Needs (CPITN). Data regarding dental attendance were collected through interviews. Spearman’s correlation analysis was performed at the p < 0.05 significance level. Results and Discussion: Oral health awareness was significantly associated with dental caries experience and periodontal status (p value< 0.001). Participants with higher awareness tended to have lower DMF-T scores and better periodontal conditions. However, no significant association was found between oral health awareness and dental attendance. These findings indicate that awareness contributes to better oral health status but does not necessarily lead to routine utilization of dental services. Conclusion: Oral health awareness was associated with dental caries experience and periodontal status but not with dental attendance among Prolanis participants. The findings suggest an awareness–action gap, suggesting that awareness alone may be insufficient to promote regular dental visits.